(The Role of Bank Deposit Security Companies in Compensating Depositors (A study in Iraqi law - طعمة سهام سوادي (Journal of Legal Sciences, 2019)
Given the fear felt by depositors whenever a financial crisis hits the banking sector, the idea of establishing institutions to compensate depositors in case the banking institution where they hold accounts is liquidated has been proposed. Advanced countries have worked on creating institutions that compensate depositors should their banks are liquidated because of financial problems. Iraq is one of these countries. It promulgated the Bank Deposit Guarantee System No.3 of 2016, whereby companies called bank deposit security companies were established to compensate depositors.